Maternal vitamin D intake and mineral metabolism in mothers and their newborn infants. Issue 6232 (5th July 1980) - Cockburn, F; Belton, N R; Purvis, R J; Giles, M M; Brown, J K; Turner, T L; Wilkinson, E M; Forfar, J O; Barrie, W J; McKay, G S; Pocock, S J
Abstract : Pregnant women receiving daily supplements of 400 IU (10 microgram) of vitamin D2 from the 12th week of pregnancy had plasma calcium concentrations higher at 24 weeks but similar at delivery to those in control pregnant women who did not receive the supplements. Infants of the women receiving the supplements had higher calcium, lower phosphorus, and similar magnesium concentrations on the sixth day of life and a lower incidence of hypocalcaemia than infants of the control women. Plasma concentrations of 25-hydroxycholecalciferol, which showed a seasonal variation, were higher in mothers and infants in the treated group. Cord-blood calcium, magnesium, phosphorus, and 25-hydroxycholecalciferol concentrations correlated with maternal values at delivery. Breast-fed infants had higher calcium and magnesium and lower phosphorus and 25-hydroxycholecalciferol concentrations than artificially fed infants. A defect of dental enamel was found in a high proportion of infants (many of whom had suffered from hypocalcaemia) born to the control women. These results suggest that vitamin D supplementation during pregnancy would be beneficial for mothers, whose intake from diet and skin synthesis is appreciably less than 500 IU of vitamin D daily.